Congenital abdominal wall defects and cryptorchidism: a population-based study - Raitio Arimatias; Syvänen Johanna; Tauriainen Asta; Hyvärinen Anna; Sankilampi Uulla; Gissler Mika; Helenius Ilkka (SPRINGER, 2025)
Purpose Several studies have reported high prevalence of undescended testis (UDT) among boys with congenital abdominal wall defects (AWD). Due to rarity of AWDs, however, true prevalence of testicular maldescent among these boys is not known. We conducted a national register study to determine the prevalence of UDT among Finnish males with an AWD. Methods All male infants with either gastroschisis or omphalocele born between Jan 1, 1998 and Dec 31, 2015 were identified in the Register of Congenital Malformations. The data on all performed operations were acquired from the Care Register for Health Care. The register data were examined for relevant UDT diagnosis and operation codes. Results We identified 99 males with gastroschisis and 89 with omphalocele. UDT was diagnosed in 10 (10.1%) infants with gastroschisis and 22 (24.7%) with omphalocele. Majority of these required an operation; 8/99 (8.1%) gastroschisis and 19/89 (21.3%) omphalocele patients. UDT is more common among AWD patients than general population with the highest prevalence in omphalocele. Conclusions Cryptorchidism is more common among boys with an AWD than general population. Furthermore, omphalocele carries significantly higher risk of UDT and need for orchidopexy than gastroschisis. Due to high prevalence testicular maldescent, careful follow-up for UDT is recommended.